COMMUNICATION TECHNIQUES OF KH NAJIH AHJAD IN THE COURT OF DA'I PONDOK MASKUMAMBANG ISLAMIC BOARDING SCHOOL - Aan Handriyani; Ahmad Chandra (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2022)
Research Objectives: To find out the communication techniques of KH. Nadjih Ahjad in the cadre of preachers at the Maskumambang Islamic Boarding School. Methods, this research includes field research with qualitative methods with the aim of getting a complete picture of the object of this research. Research Results, KH. Nadjih Ahjad uses various communication techniques in conducting preacher cadres, namely informative techniques, perfesive techniques, instructive techniques and humanist techniques.